DEMOKRATISASI MELALUI TATA KELOLA DANA DESA (Studi Tentang Interaksi Para Pihak Dalam Pengelolaan Dana Desa di Desa Golo Lebo, Kecamatan Elar, Kabupaten Manggarai Timur) - Stefanus Naor Sirabura; Sutoro Eko Yunanto (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
The problem of managing Village Funds is conditional on the interests of the elite fighting over it. But behind the contestation between the elites, the Village is able to form a democratic government. This study examines the construction of the phenomenon of village democratization through Village Fund Management in Golo Lebo Village, East Manggarai Regency. The research method uses a constructivism approach to interpret, give construction and meaning to the phenomenon as a whole. Primary data was collected using observation, interview, discussion and documentation techniques. Secondary data obtained through books, journals, documents, online media and photos. The results of the study show: First, the Village Fund establishes an accountable Village Head. Before the Village Fund, the leadership of the Village Head had the character of a ruler, regressive and conservative. In the era of Village Funds, the Village Head is able to become a father for the people, legitimacy is rooted in the people and is progressive. Second, the Village Fund obliges all elements of the Village to work together to realize the interests of the Village. Cooperation between Village parties is carried out through various formal and informal forums. These forums become an arena for village parties to negotiate. Third, the Village Fund forms the representation function of the Village Consultative Body. The Village Consultative Body is able to become a bridge between the community and the village government, as well as being a partner of the village government.